AB1315-HPR HYPERBARIC OXYGEN THERAPY IN FIBROMYALGIA PATIENTS – DOUBLE-BLIND PROSPECTIVE CLINICAL TRIAL. (2nd June 2020) - Raffeiner, B.; Ometto, F.; Astorri, D.; Botsios, C.; Pulga, G.
Abstract : Background: Hyperbaric Oxygen Therapy (HOT) proved effective in improving of symptoms of patients affected by fibromyalgia syndrome (FMS) [1]. Objectives: The objective of the present study was to evaluate the effectiveness of HOT compared to hyperbaric treatment with no oxygen therapy (PBO) in the symptoms and working ability in FMS. Methods: We conducted a prospective trial in employed patients with FMS, randomly assigned to HOT or PBO. Patients and evaluating clinicians were blinded to the treatment. HOT arm comprised 40 sessions, 5 days/week, 120 minutes, 100% oxygen at 2ATA; PBO comprised the same sessions without oxygen. Evaluations were at baseline, after 4 (T1) and 8 weeks (T2). Parameters considered were: socio-demographics, biochemistry, clinical evaluation and patient-reported outcomes (PROs). Baseline assessment included questions BELIEF (how much do you hope to improve with this treatment) and HOPE (how much do you expect to improve with this treatment), with VAS response. Spearman's, Mann-Whitney's, Kruskal-Wallis and Fisher's Exact test were used. Results: 12 patients were included and completed the study, 6 in each arm (Tab. 1). No significant difference was observed in clinical measures or PROs at T1 and T2 between HOT and PBO arms, except for Working Productivity and Activity Impairment Questionnaire (WPAI) (result III) (Tab. 2). In both arms, disease duration was associated with worse PROs (Widespread pain index r=0.59, p=0.037, Severity Score r=0.81, p=0.025); higher BMI with improvement in function at T2 (r=0.63, p=0.027); higher baseline scores in BELIEF with reduction symptoms number (r=-0.67, p=0.021), higher scores in HOPE with reduction in Health Assessment Questionnaire (r=-0.057, p=0.039) Conclusion: 8-week HOT treatment does not substantially improve symptoms in FMS compared to PBO. All patients on hyperbaric treatment may experience amelioration of symptoms: other factors should be considered, including beliefs and expectations on the treatment. References: [1]DOI:10.1371/journal.pone.0127012 Disclosure of Interests: None declared